Factors affecting foreign direct investment (FDI) in Malaysia compared to China and India / Johan Ariff Jafri - Ariff Jafri, Johan (2017)
Foreign direct investment has become a necessity for any developing country in the world. It is an important element for a nation civilization and development. Hence, a continuous and reliable inflow of FDI is needed to ensure the prosperity of the country. Due to the uncertainties in the flow of FDI, a research has been conducted to identify the relationship between rate of inflation, growth domestic product (GDP), interest rate and money growth and towards FDI. The data for all variables including FDI are collected and compiled since 2008 until 2015. In achieving the research objectives, four methods were used. They were unit root test, Multicollinearity test, normality test, Heteroskedasticity test: white, correlation test: Breusch-Godfrey serial correlation LM and multiple linear regression models.